COMPARATIVE STUDY OF ACTIVE MASS DAMPER APPLICATION ON 20-STORY STEEL FRAME STRUCTURE USING CONTROL OPTIMAL AND POLE PLACEMENT ALGORITHM - Anthony Toti, Sebastian
Earthquake is natural event that able to produce a threat to the building structure. A structure designed conventionally relies solely on its mass and rigidity to withstand the earthquake loads. Along with the times, the conventional design can not always fulfill the increasing human needs such as tall or slim buildings. Conventional designed structures are still vulnerable to withstand strong earthquake excitations. This leads to the emergence of smart structure technology in form of control system which helps structure to dissipate energy from the dynamic loads. This final project report discusses active control system more specifically about active mass damper. This system is applied on 20-story steel frame structure excited by three earthquake loads which are El Centro 1940, Kobe 1995, and Northridge 1994. The algorithm used as control algorithm of active mass damper system are control optimal and pole placement algorithm. The analysis of structure’s displacement responses are compared based on the responses without control and responses by control optimal and pole placement algorithm. The results of structure’s displacement responses reduction for the three earthquakes using both control optimal and pole placement algorithm give satisfactory reduction that relatively similar and also need similar control forces for both algorithm. The application of active mass damper system on 20-story steel frame structure proved to be effective to reduce structure’s displacement responses..